PELAKSANAAN PROGRAM DERADIKALISASI DI INDONESIA - Ivana Kartika Dinansi, Clarissa Ivana; Wahyudi, Fendy Eko (Journal of International Relations, 2018)
This study aims to find out how the Government of Indonesia implements itsderadicalization programme, more specifically to know to what extent its implementationis. This study is based on concerns about the fate of deradicalization programme ascountries’ few options to combat the terrorism in a soft way. Whereas, the officialauthorized’s of the more-advanced-countries than Indonesia claim succedd on it, at the endthey fail to give any proof of their achievement. Whilst Indonesia, who is still new to joinalso claim succedd just like any other country else, it is later known in this study thatIndonesia still has not succeded in achieveing its goal in doing deradicalization. Instead,the study suggests that what is thought to be the success of deradicalization is actually thedisengagement of violence. The study’s suggestion itself is obtained after having doneintervies with various parties who are considered to be representative and have it analyzedwith process-tracing technique.